Capital fluidity, Amazonian cities collapsing: notes on the energy and humanitarian crisis in the state of Amapá - Frabetti, Giancarlo (Geografares, 2020)
This text aims to discuss the foundations of the energy and humanitarian crisis that, in early November 2020, affected the state of Amapá. In order to achieve this goal, we firstly present how the process of Amapá's integration with the National Interconnected System (SIN) took place, and then point out the technical weaknesses that incurred in the interruption of the energy supply in the state. In parallel, we discuss the business structure and financial logic involved in the poor provision of the service offered by the company responsible for the Macapá substation. Finally, we introduce some information about the political causes and consequences of the blackout, raising questions about the privatization process of urban infrastructures whose functioning is essential to life in Amazonian cities.
Keywords: Amazon; National Interconnected System; financialization; privatization